PENGARUH CITRA PERUSAHAAN, PERSEPSI HARGA DAN KUALITAS LAYANAN TERHADAP PROSES KEPUTUSAN PEMBELIAN PRODUK DI SUPERMARKET GELAEL (Studi Pada Supermarket Gelael Cabang Mall Ciputra Kota Semarang) - Heru Fajrul Akbar Wasngadiredja, 14.05.51.0273; Sutedjo, Bambang (Students' Journal of Economic and Management, 2018)
ABSTRACT The purpose of this research is to know and analyze the influence of each variable of corporate image, perception of price, and quality of service to decision process of product purchase at supermarket Gelael. The population in this research is the consumers who buy products in supermarkets Gelael which has branch in Mall Ciputra Semarang. The sampling technique in this research uses purposive sampling, because in determining the sample based on certain criteria, namely: People who make the process of purchasing products in the supermarket Gelael Branch Mall Ciputra in Semarang city and aged over 18 years. Analyzer used is multiple linear regression analysis. The results of the analysis can be concluded, that: corporate image has a positive and significant effect on product purchasing decision process in supermarket Gelael. Price perceptions have a positive and significant effect on product purchasing decision process in supermarket Gelael. Quality of service has a positive and significant effect on product purchase decision process at Gelael supermarket. Keywords: company image, price perception, service quality and purchasing decision process.